(untitled) (Armonk, NY, 1986)
Much of the history of postwar Japan has been one of gradual erosion of local autonomy and reestablishment of central bureaucratic authority, a process particularly evident in matters of police and education. Most of the chapters of this book interpret the process of bureaucratization and centralization as inimical to popular democracy.
Keywords: Civil rights,Democracy; History,History; Japan